2023
DOI: 10.1108/mip-05-2023-0198
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling consumer behavior in marketing: a meta-analytic structural equation modeling (Meta-SEM) of the model of goal-directed behavior (MGB)

Pankaj Vishwakarma,
Malaya Ranjan Mohapatra

Abstract: PurposeUnderstanding consumer behavior across various contexts within marketing has long been the focus of studies. Although many models are used in explaining consumers' behavior, one of these is the Model of Goal-Directed Behavior (MGB), which is becoming prominent in explaining consumers' behavior in marketing. Given its popularity, prior research on MGB has shown inconsistent outcomes regarding the casual association of MGB variables. To overcome this, the authors have adopted a meta-analytic review of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 77 publications
0
1
0
Order By: Relevance
“…Therefore, the MGB, mainly designed to anticipate goaloriented behaviour, is undeniably an appropriate choice (Chiu and Choi, 2018). Furthermore, this study incorporates descriptive norms in MGB as an additional factor influencing Intention, as previous studies have demonstrated that descriptive norms affect desire, which ultimately influences user intentions (Arora et al, 2021;Vishwakarma and Mohapatra, 2023).…”
Section: Theoretical Foundation 21 Integrating Mgb and Risk Theory In...mentioning
confidence: 99%
“…Therefore, the MGB, mainly designed to anticipate goaloriented behaviour, is undeniably an appropriate choice (Chiu and Choi, 2018). Furthermore, this study incorporates descriptive norms in MGB as an additional factor influencing Intention, as previous studies have demonstrated that descriptive norms affect desire, which ultimately influences user intentions (Arora et al, 2021;Vishwakarma and Mohapatra, 2023).…”
Section: Theoretical Foundation 21 Integrating Mgb and Risk Theory In...mentioning
confidence: 99%